Association of Single-nucleotide Polymorphisms rs2243250 of IL4 gene in Diabetes Type 1 Patients with Acute Tonsillitis - Zainab khidhair Hussain; Bushra Rashid Ibrahim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Diabetes mellitus type 1 one of diseases which is a difficult metabolism condition, it is characterize highlevel of glucose in of the human blood stream and is a consider prolonged autoimmune disease alignmentsever inflammatory factor. The newest studies reveal that innate immunity high role in diabetes type1. Thesamples in this study consist of (135) Iraqi male with diabetes type 1 with acute tonsillitis in three group(G1: 4-18 years, G2: 11-18 years and control) all samples diagnosed by biochemical methods added to theclinical method. Alleles were determined by amplification of the polymorphic site by real time polymerasechain reaction. The result of genotyping study of rs2243250 of IL4 revealed that the T allele frequencyshowed (0.42 %), (0.41%) and (0.69%) in groups G1,G2, control respectively, while the result revealed thatthe allele frequency C in groups G1,G2, control was (0.58%), (0.59%) and (0.31%) respectively. The studycan be concluded that the genetic variation of rs2243250 of IL4 gene was associated with diabetes mellitustype1 comparison in control (healthy women) in Iraqi men.